METHOD OF WEBINAR ORIENTED PLATFORMS APPLICATION IN HIGH SCHOOL LEARNING PROCESS OF COMPUTER SCIENCE - Bogachkov Ю.М.; Tsarenko В.О. (Journal of Information Technologies in Education (ITE), 2013)
This article explores some components of method of webinar oriented platforms application in computer science of high school. The webinar’s forms and methods of computer science teaching are analyzed. The classification of teaching methods of computer science in virtual environment based on information and communication technologies is developed.